The Effect of Counseling Program According to Neuro – Linguistic Programing for Improving General Appearance and Personality Competencies in Physical Educators - Fahem, Hani; Ibraheem, Huaida (Journal of Physical Education, 2022)
The research aimed at designing a counseling program according to neuro – linguistic programing for improving general appearance and personality competences of physical educators as well as identifying the effect of this program on the development of general appearance and personality competencies of physical educators. The researchers used two – group experimental program on fourth Year College of physical education and sport sciences students. Two sections served as the controlling group and the experimental group while three sessions of (90) students served as scale subjects and finally the pilot study subjects were (25) fourth year students. The reseace4rhc concluded that the counseling program according to neuro – linguistic programing developed general appearance and personality competencies in the experimental group compared to the controlling group.